'Pure' Time Preferences Are Irrelevant to the Debate over Time Bias: A Plea for Zero Time Discounting as the Normative Standard. Issue 3 (3rd July 2021) - Greene, Preston
ABSTRACT: I find much to like in Craig Callender's [2022] arguments for the rational permissibility of non-exponential time discounting when these arguments are viewed in a conditional form: viz., if one thinks that time discounting is rationally permissible, as the social scientist does, then one should think that non-exponential time discounting is too. However, time neutralists believe that time discounting is rationally impermissible, and thus they take zero time discounting to be the normative standard. The time neutralist rejects time discounting because they think it is rationally impermissible to prefer to live a worse life in expectation because of arbitrariness. Callender's attack on the time-neutralist position is the following: the time-neutralist's non-arbitrariness intuition assumes the existence of nonexistent 'pure' time preferences. In response, I aim to clarify the time-neutralist position and show that the non-arbitrariness argument does not rely on the existence of pure time preferences. Instead, the debate between time neutralism and permissivism about time discounting boils down to a methodological question: can we ever criticize the content of preferences? If so, we should embrace time neutralism.